Metabolic reprogramming of naïve regulatory T cells by IL-7 and IL-15 promotes their persistence and performance upon adoptive transfer - Jessica Filoni; Arianna Ferrari; Tatiana Jofra; Anna Rita Putignano; Lorenzo Da Dalt; Susanna Cesarano; Carla Di Dedda; Fabrizia Bonacina; Federica Marchesi; Danilo Norata; Chiara Bonini; Lorenzo Piemonti; et al. (Communications Biology)
Abstract Tregs for adoptive therapy are traditionally expanded ex vivo using high doses of IL-2. However, the final Treg product has limited survival once infused in patients, potentially affecting therapeutic effectiveness. Here, we tested a novel expansion protocol in which highly purified naïve Tregs were expanded with a combination of IL-7 and IL-15, in the absence of IL-2. The final Treg product was enriched with cells displaying an immature CD45RA+CD62L+CD95+ phenotype, reminiscent of conventional memory stem T cells. The combination of IL-7 and IL-15 confers Tregs a glycolytic metabolism and improved metabolic fitness, characterized by an increased capacity to adapt metabolism according to glucose and oxygen availability. Tregs expanded with IL-7 and IL-15 showed longer persistence and an improved capacity to control xeno-GvHD in NSG mice. This work suggests that metabolic reprogramming induced by IL-7 and IL-15 provides better Treg performance for adoptive therapy.